EKSPLORASI SISA PERTENUNAN SERAT SUTERA DENGAN TEKNIK MAKRAME PADA PRODUK FASHION - Hady, Devi Candraditya; Widiawati, Dian (Craft, 2012)
Abstrak Penelitian ini membahas tentang potensi sisa pertenunan serat sutera sebagai salah satu komoditi yang memiliki nilai tinggi. Sejauh ini pemanfaatan limbah benang dari industri pertenunan serat hanya terbatas digunakan sebagai bahan baku benang saja. Namun, volume sisa pertenunan serat sutera yang berlimpah terkadang juga dimusnahkan dengan cara dibakar agar tidak terlalu banyak memakan tempat. Belum banyak orang yang tertarik mengolah sisa pertenunan serat sutera sutera tersebut  menjadi barang siap pakai yang bernilai lebih. Studi kasus dilakukan di industri pertenunan sutera Tarogong, Garut, Jawa Barat. Melalui eksperimentasi material sisa pertenunan serat sutera dengan berbagai karakteristiknya, sisa pertenunan serat sutera tersebut ternyata dapat digunakan sebagai salah satu produk tekstil alternatif. Pada penelitian tahap awal ini dilakukan berbagai cara pengolahan sisa pertenunan serat sutera menjadi bahan baku serat tekstil, khususnya dengan teknik makrame.  Dengan melakukan pengolahan terhadap sisa pertenunan serat sutera diharapkan dapat dapat menjadi salah satu solusi alternatif dalam upaya pengurangan sampah yang diakibatkan oleh industri pertenunan yang ada di hampir beberapa sentra serat. Pengolahan sisa produksi pertenunan juga diharapkan memaksimalkan potensi dan meningkatkan kualitas juga nilai estetika sehingga dapat menjadi salah satu alternatif bahan tekstil dan produk fashion yang berkualitas. Kata Kunci : eco fashion,  limbah, makrame, serat sutera  Abstract The impact of various phenomena and issues upon the environtment that exist today should make the change in mindset of society of these days upon beholding the state of the natural environment. One of the efforts in supporting the environmental conservation movement was to manufacture the eco-fashion products which one of them was the use of weaving production residual material on reproducing the textile and fashion products. The case studies of this research discussed the potential of the weaving residual of silk fibers reproduced into such commodity with high value. So far, the utilization of this yarn waste from fiber weaving industry was only limited to be used as a raw material for the yarn. However, the remaining volume of the silk fiber was so overwhelming that sometimes be destroyed by fire so as to reduce the consuming of place. The availability of this waste was so abundant, especially in the area of Tarogong, Garut regency, West Java where not many people were keen to processing the rest of the silk weaving waste into ready-made goods with high value. Through the deep exploration of silk fiber weaving waste with its various characteristics, this weaving waste could apparently be used as an alternative textile products. On the early stage of research, many ways of tabulation were executed to achieve the manner of good textile product material, performed especially by the technique of macrame.The execution of the tabulation process to the silk fiber weaving waste as the main ingridient was to be expected to maximize the potential and also to improve the quality as well as the aesthetic value hence it could become one alternative for high quality textile material and fashion products. The tabulation process of the weaving waste was also expected to be able to facilitate an alternative solution in the effort of reducing the waste caused by the weaving industry in  nearly many fiber manufacturing centrals. Also, it could provide a great opportunity for small household industries which were expected to become a major players in tabulation process for the further weaving wasteproducts and also one which would have an impact on the economic empowerment of the community at large. Keywords : eco-fashion, macrame, silk fiber, waste product